PENGARUH TEKNIK SELF TALK TERHADAP KEPERCAYAAN DIRI SISWA KELAS IX SMP NEGERI 9 TARAKAN - Khairina Rasna Indriana; Siti Rahmi (Jurnal Bimbingan dan Konseling Borneo, 2019)
This study uses a quantitative type with a quasi-experimental approach to nonequivalent control group design. The study population amounted to 244 students, with purposive sampling sampling, the provisions of the study sample obtained 20 students divided into 10 experimental groups and 10 control groups. The instrument used in the form of student confidence scale that has been through validation testing from expert judgment and declared valid. Reliability of the confidence scale was tested using Alpha Cronbach and obtained a coefficient of 0.786 which showed a high level of reliability. Hypothesis analysis using the Wilcoxon test through the SPSS version 24.00 for windows program. Based on the results of statistical data analysis results of the calculation of the t-test using SPSS version 24.00 for windows obtained a significance value = 0.000 ɑ = 0.05. this shows a significant value of less than 0.05 can be concluded that the hypothesis is accepted, which means that there is an effect of self talk techniques on the confidence of class IX students in Tarakan 9 Middle School Academic Year 2018-1919.  Keywords: Self Talk, Student Confidence